Single-Center Experience with Minimally Invasive Mitral Operations through Right Minithoracotomy - Pojar, Marek; Vojacek, Jan; Karalko, Mikita; Turek, Zdenek (Annals of thoracic and cardiovascular surgery, 2019)
BACKGROUND: To report single-institution experience with minimally invasive mitral valve operations through the right minithoracotomy over a 5-year period. METHODS: Patients who underwent minimally invasive mitral valve surgery (MIMVS) between January 2012 and December 2016 were included. Clinical follow-up data were collected in a prospective database and analyzed retrospectively. RESULTS: Data from 151 patients were assessed (mean age, 63.4 ± 9.7 years; 55% were females). Overall 30-day mortality was 0.7% (n = 1). Mean operating time, cardiopulmonary bypass, and aortic cross-clamp times were 254.9 ± 48.7, 140.5 ± 36.1, and 94.8 ± 27.0 minutes, respectively. Associated procedures were tricuspid valve annuloplasty (37.1%, n = 56) and closure of atrial septal defect (6.0%, n = 9). Cryoablation was performed in 43.7% of patients (n = 66). One patient (0.7%) required conversion to median sternotomy and six patients (4.0%) underwent re-explorations due to bleeding. Median postoperative hospital stay was 12 days. Overall survival at 5 years was 94.1% ± 2.0%. Freedom from reoperation was 94.6% ± 2.9% at 5 years. CONCLUSIONS: MIMVS is a feasible, safe, and reproducible approach with low mortality and morbidity. Mitral valve surgery through a small thoracotomy is a good alternative to conventional surgical access.
Keywords: mitrální insuficience; Humans; lidé středního věku; echokardiografie; minithoracotomy; mitrální chlopeň; mitral valve repair; studie proveditelnosti; Echocardiography; Female; rizikové faktory; chirurgická náhrada chlopně; Aged; databáze faktografické; Time Factors; výsledek terapie; senioři; lidé; Thoracotomy; reoperace; Mitral Valve; minimally invasive; Mitral Valve Annuloplasty; časové faktory; Databases, Factual; Mitral Valve Insufficiency; Postoperative Complications; pooperační komplikace; anuloplastika mitrální chlopně; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Treatment Outcome; Czech Republic; mitral valve; retrospektivní studie; endoscopic surgery; Feasibility Studies; Česká republika; mužské pohlaví; Heart Valve Prosthesis Implantation; Reoperation; torakotomie; Risk Factors